Access to Enantioenriched Organosilanes from Enals and β‐Silyl Enones: Carbene Organocatalysis. (15th March 2018) - Zhang, Yuxia; Huang, Jie; Guo, Yingying; Li, Lin; Fu, Zhenqian; Huang, Wei
Abstract: Herein, an efficient route to enantioenriched organosilanes, containing two consecutive stereogenic centers, from enals and β‐silyl enones under carbene organocatalysis is described. Under mild reaction conditions, this transition‐metal‐free strategy exhibits a broad substrate scope, and excellent diastereo‐ and enantioselectivity. Abstract : Eine Carben‐katalysierte formale [4+2]‐Anellierung von Enalen mit β‐Silylenonen unter milden Reaktionsbedingungen führt zu einem diversen Satz an enantiomerenangereicherten Organosilanen mit zwei aufeinanderfolgenden Stereozentren. Die übergangsmetallfreie Strategie liefert die Produkte in guten Ausbeuten mit exzellenten Diastereo‐ und Enantioselektivitäten.